CAPRIPOXVIRUS DISEASES IN INDIA - M. R. Omkar; Amitha Reena Gomes; D. Ratnamma; B.M. Chandranaik; G. Sudha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The genus Capripoxvirus (CaPV) comprises three members namely, sheep pox virus (SPPV), goat pox virus (GTPV) and lumpy skin disease virus (LSDV) affecting sheep, goats and cattle, respectively. Capripoxvirus infections produce similar symptoms in sheep and goats, and the three viruses cannot be distinguished serologically. The Capri pox virus disease is an economically important notifiable disease of cattle, sheep and goats (OIE, 2018). This article reviews about the current scenario of Capri pox disease and the better opportunities for prevention and control of disease. Recent outbreaks of the disease have caused the major economic loss in most of the countries including India.